"Resistance is Futile!": The Ironies of Danielic Resistance to Empire. (April 2017) - Newsom, Carol A.
This essay explores how the discourses of imperial power and of the subordinated peoples are worked out in relation to one another in the book of Daniel. In resisting the empires that dominated Israel, the book of Daniel draws on imperial imagery of power exercised by human rulers, and thus inadvertently re-inscribes the imperial cycle by reifying idolatrous human institutions. This essay considers the alternative image of the rock hewed out—not by human hands—that undermines idolatrous images of power. To break free of imperialism, one must be open a radical new idea that deconstructs imperialism.